The relationship between dental fear, anxiety and sociodemography in Jakarta, Indonesia - Lisa Prihastari; Rima Ardhani Iswara; Ghina Al Afiani; Fajar Ramadhan; Mega Octaviani; Willy Anugerah Hidayat; Muhammad Al Faqih; Ahmad Ronal (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2020)
Background: The anxiety associated with dental visits is one of the obstacles preventing dentists from improving oral health and is also a significant predictor of dental visit evasion, which is frequently observed in Indonesia. Purpose: To identify the level of dental fear and anxiety in the population of Jakarta, Indonesia and establish the relationship with sociodemographic factors. Methods: A cross-sectional method was used with a sample size of 1811 respondents aged 17–65 years old who were asked to complete the validated Indonesian versions of modified dental anxiety scale (MDAS) and dental fear scale (DFS) questionnaires. The data obtained was then analysed using nonparametric and chi-square tests. Results: The prevalence of subjects with moderate to high dental anxiety and fear was 16.3% (295 respondents) and 36.1% (654 respondents), respectively. The primary sources of dental fear and anxiety were dental drilling and anaesthesia before tooth extraction. The results of the nonparametric and chi-square tests show that both are significantly related to gender, age, educational status, income level, insurance and history of dental visits (p = < 0.05). Conclusion: Several sociodemographic factors are associated with dental fears and anxiety among the participants in Jakarta, Indonesia.